The wrong(‘s) place: discrimination against lesbians, gays, and bisexual women in medical education - Moretti-Pires, Rodrigo Otávio; Grisotti, Marcia (Saúde e Sociedade, 2022)
This article aims to analyze the experience of medical students who identify themselves as lesbians, gays, and bisexuals inside the professional health corporation of highest social prestige in contemporary Brazilian society, the Medicine. The categories found show that the undergraduate course has a hidden curriculum that operates in the logic of excesses, with a conservative, masculinist, and heteronormative medical model. People of the LGBTI+ community are made invisible, both in terms of curriculum and in social relations, in a process of excessive and constant surveillance of students to adapt to a model that privileges heterosexual men, whereas the rest are considered abject.